1997
DOI: 10.1080/026990597123773
|View full text |Cite
|
Sign up to set email alerts
|

Impact of childhood brain injury on work and family finances

Abstract: Parents of children who suffer brain injuries are often surprised by the extent to which work and family finances are disrupted. In this paper, work and financial problems are described, predictors are identified, and ways to minimize problems are discussed. Eighty-two children treated at two Massachusetts trauma centres were given an extensive battery of medical, functional, and psychosocial tests during hospitalization. At 1 and 6 months post-discharge they were retested and their parents were surveyed about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This finding remained significant even after controlling for estimated SES and is consistent with previous research demonstrating that income and financial considerations are significant predictors of caregiver burden following brain injury. The fact that this relationship was not depleted by accounting for SES in the analysis highlights the importance of adequate financial resources beyond other variables typically associated with SES in facilitating positive outcome after brain injury [31, 61]. However, the variable of financial resources may, in this case, merely be a proxy for other environmental influences (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding remained significant even after controlling for estimated SES and is consistent with previous research demonstrating that income and financial considerations are significant predictors of caregiver burden following brain injury. The fact that this relationship was not depleted by accounting for SES in the analysis highlights the importance of adequate financial resources beyond other variables typically associated with SES in facilitating positive outcome after brain injury [31, 61]. However, the variable of financial resources may, in this case, merely be a proxy for other environmental influences (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Osberg et al [61] argue that the increases in financial strain after paediatric TBI affect the family system in a negative manner by exacerbating overall family stress, eventually leading to greater family disruption. Work by Montgomery et al [62] indicated that financial difficulties are experienced by at least 30% of families even up to 3 years post-injury and research with adults suggests that decreased family financial resources have a direct and deleterious impact on outcome as well as having an indirect/moderating effect on caregiver burden [63].…”
Section: Discussionmentioning
confidence: 99%